Optimized bisubstrate inhibitors for the actin N-terminal acetyltransferase NAA80 - Myklebust, Line M.; Baumann, Markus; Støve, Svein I.; Foyn, Håvard; Arnesen, Thomas; Haug, Bengt Erik (Frontiers in Chemistry, 2023)
Acetylation of protein N-termini is one of the most common protein modifications in the eukaryotic cell and is catalyzed by the N-terminal acetyltransferase family of enzymes. The N-terminal acetyltransferase NAA80 is expressed in the animal kingdom and was recently found to specifically N-terminally acetylate actin, which is the main component of the microfilament system. This unique animal cell actin processing is essential for the maintenance of cell integrity and motility. Actin is the only known substrate of NAA80, thus potent inhibitors of NAA80 could prove as important tool compounds to study the crucial roles of actin and how NAA80 regulates this by N-terminal acetylation. Herein we describe a systematic study toward optimizing the peptide part of a bisubstrate-based NAA80 inhibitor comprising of coenzyme A conjugated onto the N-terminal of a tetrapeptide amide via an acetyl linker. By testing various combinations of Asp and Glu which are found at the N-termini of beta- and gamma-actin, respectively, CoA-Ac-EDDI-NH2 was identified as the best inhibitor with an IC50 value of 120 nM.